Concept of due freedom necessary for the reception of ordination - Leszczyński, Grzegorz (Prawo Kanoniczne, 2021)
The act of receving ordination as a human act requires the canididate to have the mental capacity necessary to express it. This ability means that a person, at the time of ordination, is able to make a conscious and voluntary decision about priestly life and is able to fulfill the obligations arising from ordination. Consequently, the lack of this capacity means a natural incapacity to receive orders, a lack of the due freedom mentioned in can. 1026 of the CIC.